PENGARUH DUKUNGAN (ENDORSEMENT), CITRA MEREK (BRAND IMAGE) DAN KESAKSIAN (TESTIMONI) TERHADAP MINAT BELI ULANG KONSUMEN PRODUK RNC WBEAUTY MELALUI MEDIA SOSIAL INSTAGRAM - BAIQ TIRTA SEPTYNA DWI CAHYANI; H. NIZAR HAMDI; ZULKARNAEN ZULKARNAEN (GANEC SWARA, 2023)
This study aims to determine the effect of Endorsement, Brand Image and Testimony on Consumer Repurchase Interest of RNC Wbeauty Products Through Social Media Instagram, a case study in East Lombok district. This research uses quantitative research with associative approach. This data is proven by using multiple linear regression analysis. From the results of the regression equation, it is obtained that Y = 0.832 + 0.307.X1 + 0.853.X2 + 0.016.X3 so that the results of the t-test conclude that endorsement and brand image have a positive and significant effect on repurchase intention, while the testimony (Testimonials) have a negative effect on consumer buying interest by opening each t count is greater than t tabel (2,072>1,678) and (6,640>1,678) and significant (0,0440,05). In the F test, it can be concluded that the variables of Support (Endorsement) and Brand Image (Brand Image) and Testimonies (Testimony) have a simultaneous effect on Consumer Buying Interest with culculated F value greater than F tabel (34,793>3,20). From the results of the coefficient of determination, it shows that endorsement, brand image and testimonials have an effect of 69.3% on repurchase interest, while the remaining 30.7% is explained by other factors. Thus, it means that endorsement and brand image have a positive and significant effect on repurchase intention, while testimonials have no significant effect on repurchase interest